Preexisting high frequencies of memory CD8(+) T cells favors rapid memory differentiation and preservation of proliferative potential upon boosting - Fraser, Kathryn A. (2013)
Memory CD8(+) T cell quantity and quality determine protective efficacy against reinfection. Heterologous prime boost vaccination minimizes contraction of anamnestic effectors and maximizes memory CD8(+) T cell quantity, but reportedly erodes proliferative potential and protective efficacy. This study exploited heterologous prime boost vaccination to discover parameters regulating effector CD8(+) T cell contraction and memory differentiation. When abundant memory T cells were established, boosting induced only 5-8 cell divisions, unusually rapid memory T cell differentiation as measured by phenotype and mitochondrial bioenergetic function, long-lived survival of 50% of effector T cells, and preservation of proliferative potential. Conversely, boosting in situations of low memory CD8(+) T cell frequencies induced many cell divisions, increased contraction of effector cells, and caused senescence, low mitochondrial membrane potential, and poorly protective memory. Thus, anamnestic memory T cell differentiation is flexible, and abundant quantity can be achieved while maximizing protective efficacy and preserving proliferative potential.